KAJIAN ETNOBOTANI TUMBUHAN OBAT OLEH ETNIS MASYARAKAT DI DUSUN ARAS NAPAL KIRI DAN DUSUN ARAS NAPAL KANAN DESA BUKIT MAS KECAMATAN BESITANG KABUPATEN LANGKAT - Jamilah Nasution; Putri Dwi Masitah; Riyanto Riyanto (Universitas Negeri Medan, 2016)
Based on this observation, thre are 42 species of beneficial herbal plant from 27 family grown in Dusun Aras Napal Kiri and Dusun Aras Napal Kanan, Desa Bukit Mas Kabupaten Langkat. The parts of plant usefully are leave (22 species or 47,83%), rizomes ( 8 species or17,39%), latex (4 species or 8,70%), seed (3 species or 6,52%), stem and root are each (2 species or 4,35%), and flower (only 1 species or 2,17%).The Javanese is the Etnis who use the most herbal plants (34 species) whilst Karo and Batakness uses 20 species and 19 species. The wealth of the herb can be used into 4 categories sch as Medecine (60,47%), Healthcare(30,23%), Beautycare (4,65%), and medicare (4,65%). Keywords: Ethnobotany, medicinal plant, Aras Napal